La resistencia anaeróbica y su influencia en el rendimiento físico de los Árbitros Profesionales de Fútbol de la Provincia de Loja, 2023-2024. - Placencia Ganazhapa, Roberto Carlos (2024)
The present curricular integration work was carried out with the objective of developing anaerobic endurance to improve the Professional Soccer Referees' physical performance of Loja Province, 2023-2024; the approach used was mixed, with a quasi-experimental design with a correlational scope, based on inductive, deductive and analytical methods. Diagnostic instruments and tests were applied to a sample of 10 soccer referees. Therefore, after having obtained the following results, and having already applied the tests, it was evidenced that the referees are in an average of 2400m and 3000m in Cooper's Test, found at in good and very good valuation. These results are not so negative based on the table that allows us to show what rating scale is given to the participant, but undoubtedly there is room for improvement in these aspects. Based on the results obtained, a training plan was planned and applied to improve anaerobic endurance, which was structured in 9 weeks with three training sessions per week related to the improvement of physical performance. At the end of the training plan, post-tested progress in the aforementioned physical aspects was applied to the point of reaching an average of 2700 and 3100 meters, entering a rating scale of very good and exceptional. It is concluded that before the application of the training plan, there were deficiencies concerning the development of anaerobic endurance and its impact on physical performance, on the other hand, post-application of the training plan there was an improvement in these aspects, thus demonstrating the effectiveness of anaerobic endurance training. Keywords: anaerobic endurance, physical performance, soccer referees.